2002
DOI: 10.1001/archsurg.137.10.1174
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Liver Grafts in Living-Donor Adult Liver Transplantation

Abstract: Hypothesis: Few studies have investigated the results of research focused on living-donor adult liver transplantation. Different characteristics between right-and leftlobe grafts have not yet been clarified in living-donor adult liver transplantation. Left-lobe graft remains an important option, even in adult recipients. Setting: A single liver transplantation center with a long history of hepatic resection. Patients: Forty-five donors received left-lobe (n=39) and right-lobe (n=6) grafts. The clinicopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 29 publications
0
60
1
Order By: Relevance
“…The technical complexity of the use of right-lobe grafts (necessity of adequate venous drainage, frequent vascular and biliary anatomical variations complicating the implantation technique), and the presumed reduced donor morbidity are arguments which could advocate the use of left-lobe grafts in adults (35). This advantage of LL donation has been shown by an Asian survey, but not confirmed in the Western countries, presumably due to the small number of procedures performed (11,(35)(36)(37). The European Liver Transplant Registry displayed indeed only a 1-year overall graft survival rate of 41% for left lobes vs. 73% for right lobes but, to our knowledge, no graft inflow modulation was used in these patients (12).…”
Section: Discussionmentioning
confidence: 99%
“…The technical complexity of the use of right-lobe grafts (necessity of adequate venous drainage, frequent vascular and biliary anatomical variations complicating the implantation technique), and the presumed reduced donor morbidity are arguments which could advocate the use of left-lobe grafts in adults (35). This advantage of LL donation has been shown by an Asian survey, but not confirmed in the Western countries, presumably due to the small number of procedures performed (11,(35)(36)(37). The European Liver Transplant Registry displayed indeed only a 1-year overall graft survival rate of 41% for left lobes vs. 73% for right lobes but, to our knowledge, no graft inflow modulation was used in these patients (12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the size of the graft liver correlates with clinical outcome [21][22][23][24]. Kiuchi et al [22] reported that the graft survival rate in patients with GRWR of <0.8% was significantly worse than with larger GRWR.…”
Section: Discussionmentioning
confidence: 99%
“…Still, a right hepatectomy involves removing a larger mass of the liver and likely entails greater surgical stress for the recipient. In the series by Shimada et al, 3 rightlobe donors had greater serum aspartate aminotransferase and bilirubin levels postoperatively and longer hospital stays. Similar findings were noted in a nondonor model with patients undergoing hepatic resection for malignancy 4 ; recovery of liver function, according to laboratory test results, was slower and morbidity was greater in the right (versus left) hepatectomy patients.…”
Section: Donor Safetymentioning
confidence: 91%
“…In an earlier report by Ben-Haim et al 2 of 10 left-lobe recipients, 4 patients (40%) had small-for-size syndrome; of 30 right-lobe recipients, only 1 (3.3%) had a similar problem. Even in the series of Shimada et al, 3 of 39 left-lobe recipients, 12 (30.8%) had persistent hyperbilirubinemia (defined as serum bilirubin Ͼ 10 mg/dL on posttransplant day 14). That rate of hyperbilirubinemia was equivalent to the rate in their 6 right-lobe recipients, yet is higher than results generally reported in the literature for right-lobe recipients.…”
Section: Recipient Selection and Outcomementioning
confidence: 92%